Enhancing operation effectiveness by maximizing daily EBITDA as a turnaround strategy execution system to enhance operation performance and profitability - Rudy Setyopurnomo; Sudarso K. Wiryono; Yuliani Dwi Lestari; Subiakto Sukarno (Journal of Open Innovation: Technology, Market and Complexity)
Many companies struggle with strategy implementation due to the complex nature of execution. Some strategy execution systems depend on numerous indicators, making it challenging for managers to oversee effectively. Additionally, during times of financial difficulty, companies require a straightforward turnaround strategy execution system featuring clearly defined Key Performance Indicators (KPIs). This system should empower employees at all levels, fostering a shared sense of alignment and unity as the organization pursues common goals. The researchers aim to provide a simplified system for implementing turnaround strategies that ensures the company's profitability. To achieve this, they recommend utilizing daily Earnings Before Interest, Taxes, Depreciation, and Amortization (EBITDA) as the primary KPI, as it is entirely under operational control. Moreover, EBITDA can be integrated into business processes and remains solely within the purview of operations leaders and employees, thereby cultivating a sense of ownership and accountability. Once the company reaches a certain level of profitability, it can then incorporate additional KPIs. The researchers developed hypotheses based on deductive reasoning following a comprehensive literature review. They analyzed qualitative data from interviews and quantitative data from surveys. After implementing their program in a ferry company, they observed an approximate 33 % increase in revenue, a staggering 300 % surge in EBITDA, and an expansion of the EBITDA margin by over 250 %. The researchers validated their hypotheses through multiple case studies across ferry, shipbuilding, and aircraft manufacturing companies. This research contributes to the development of a straightforward turnaround strategy execution system by translating strategic programs and EBITDA targets into actionable plans for business processes daily. This approach assists leaders and employees in enhancing company culture and systems to achieve improved performance and profitability. The researchers focus on executing turnaround strategies effectively within company operations.